已知m+n=2012(m-n),则m+n/2(m-n)=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 17:03:13
已知m+n=2012(m-n),则m+n/2(m-n)=?已知m+n=2012(m-n),则m+n/2(m-n)=?已知m+n=2012(m-n),则m+n/2(m-n)=?m+n=2012(m-n)
已知m+n=2012(m-n),则m+n/2(m-n)=?
已知m+n=2012(m-n),则m+n/2(m-n)=?
已知m+n=2012(m-n),则m+n/2(m-n)=?
m+n=2012(m-n)
m+n/2(m-n)=[2012﹙m-n﹚]/2﹙m-n﹚=1006
答;m+n/2(m-n)=1006
解:因为m+n=2012(m-n),所以(m+n)/(m-n)=2012,所以(m+n)/2(m-n)=2012/2=1006。
m+n=2012(m-n)
所以原式=2012(m-n)/2(m-n)=1006
已知m+n=2012(m-n),则m+n/2(m-n)=?
已知m不等于n,且m+n=2012(m-n),则45(m-n)分之180(m+n)=?
已知1/m+1/n=1/m+n,则m*m/n*n+n*n/m*m
已知3m=2n,则m/(m+n)+n/(m-n)-n^2/(m^2-n^2)=?
已知3m=4n,则m/m+n+n/m-n-m^2/m^2-n^2=
已知5m=7n,则m/n=?,(m+n)/(m-n)=?
已知m[m(m+n)n]+n=1,则m+n的值是(
已知,m,n为自然数,且m(m-n)-n(n-m)=7,则m=?,n=?
已知m-n=8,则(m-n)²(m-n)²不好意思是m²-n²=8 (m-n)²(m+n)²
已知mn≠0,则|m|/m+|n|/n=
m/n=7/3则m+n/m-n
已知m/n=5/3,求m/(m+n)+m/(m-n)-n平方/(m平方-n平方)
已知m/n=5、,求(m/(m+n))+(m/(m-n))-(n^2/(m^3-n^2))
已知|m|=5,|n|=2 |m+n|=m+n,求m-n
已知2(m+n)=1005(m-n),45(m-n)分之180(m+n)=
已知1/m+1/n=7/(m+n),求n/m+m/nの值
已知n/m=3/5,求m+n/m
已知m²+n²=10,m*n=4,则代数式-m^3n-n^3m=